PENGERTIAN , SUMBER, DAN DASAR PENDIDIKAN ISLAM: bahasa indonesia - Hikmatul Hidayah Hidayah (JURNAL AS-SAID, 2023)
Education has a very important role, even the most important in developing Islamic civilization, in achieving the glory of Muslims will not be achieved except with Islamic education, Islamic education helps students to grow and develop through self-actualization of potential based on the moral principles of the Qur'an , knowledge and life-skills. This paper aims to analyze the meaning, sources and basis of Islamic education. In this research, the writer uses library research, which is a series of activities related to library data collection methods to obtain information data by gathering information related to the basic concepts of Islamic education. In this study, the authors used the content analysis (content study) approach. This research is in-depth discussion of the contents of written or printed information in the mass media which is used to draw conclusions through trying to find the characteristics of the message, and is carried out objectively and systematically. The data sources in this study are primary data sources from the Al-Qur'an while secondary data sources such as books, articles, etc. The results of this study are: Etymologically and terminologically, the definition of Islamic education, using the terms tarbiyah, ta'lim, and ta'dib, is in principle the same, that is, it is used to describe a process in growing and developing all human potential towards maturity, both physical, intellectual, and spiritual. The sources of Islamic Education are the Al-Qur'an, Sunnah, sayings, deeds, attitudes of friends, philosophers and ijtihad. The basis of Islamic education is the Qur'an, Sunnah, words of attitudes and actions of friends, historical basis, social basis, economic basis, political basis, psychological basis, and physiological basis.